"Hopefully This Will All Make Sense at Some Point": Meaning and Performance in Illness Blogs. (July 2018) - Heilferty, Catherine McGeehin
Aims: To analyze the narratives of illness blogs created by parents of children with cancer.Background: The profound effects of the childhood cancer experience on family members and the turn to the Internet by parents for help in the process are gaining research attention.Design: The qualitative study design involved secondary narrative analysis of 14 illness blogs: 9 by the parents of children with neuroblastoma and 5 by the parents of children with leukemia. Daily blog entries were analyzed as individual units of illness experience expression and in relation to one another to identify thematic and linguistic similarities.Methods: The initial analysis of these illness blogs resulted in identification of the quest for balance as a primary theme. Narratives in parents' childhood cancer illness blogs illustrated themes of performance. During this initial analysis, however, the author repeatedly asked, "Why are they writing this? And why publish this?" A second analysis of the data answered these questions of why parents blog about the experience.Results: Narrative analysis resulted in the discovery of 6 main reasons that parents wrote and published the childhood cancer experience online: to report, explain, express, reflect, archive, and advocate.Conclusion: The analysis suggests that incorporation of parent writing may improve family-–provider communication, enhance the family-health care professional relationship, enhance safety by preventing medical errors, improve reporting of clinical trial data such as adverse events, and improve satisfaction.